Fostering Literacy Culture through 5-Minute Reading Habit: A Community Service Initiative at Elementary School 034816 Jambu Mbellang - Ernasari; Ester Julinda Simarmata; Rosdiana Samosir (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service aims to develop a culture of literacy at SD Negeri 034816 Jambu Mbellang through the habit of reading for 5 minutes. Involving instructors, students and parents, this program focuses on producing positive changes in reading behavior among participants. By carrying out preparatory analysis and planning, we explain the literacy situation in schools and propose relevant strategies. The results of implementing this program show a major change in children's enthusiasm for reading, as well as growth in literacy skills. Ongoing reviews and regular monitoring can identify supporting factors and barriers to program performance. Outreach to parents and their involvement in children's literacy instruction is critical in establishing a supportive atmosphere at home. Workshops and additional training for teachers and parents provide insight and practical solutions to improve literacy learning. The success of this program is not only seen in improving students' reading abilities, but also in changes in attitudes, active participation of parents, and growth in teacher skills. These results suggest that bringing the entire school community together can foster a positive and sustainable literacy culture. It is hoped that this success will provide inspiration and input for similar efforts to improve literacy in other schools.